Rodinný dům s provozovnou - Chadima, Zdeněk (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Bakalářská práce řeší projektovou dokumentaci pro provedení stavby rodinného domu s provozovnou ve Skutči. Provozovnou je fotoateliér s grafickým studiem. Dům je určen pro 4 až 5 člennou rodinu a má tři podlaží. Podzemní podlaží je vyhrazeno pro provozovnu, zbylé dvě nadzemní podlaží tvoří rodinné bydlení. Jednotlivá patra nemají stejný půdorys. Konstrukční systém je zděný, převážně z keramických tvárnic. Zastřešení je z části provedeno pultovou střechou, zčásti střechou plochou vegetační. Pozemek, kde je objekt situován má mírný sklon.

The bachelor thesis deals with the design documentation for construction of a house with an establishment in the Skuteč. The establishment is a photographic studio with a graphic studio. The house is designed for a 4 to 5-member family and has three floors. The underground floor is reserved for the establishment, the other two floors are family housing. No floor has the same floor plan. The structural system is walled, mostly of ceramic blocks. Part of the roof is made of a shed roof, partially flat roof vegetation. The land where the object is located has a gentle slope.
Family House with an establishment
Keywords: Bakalářská práce; rodinný dům s provozovnou; pultová střecha; zděný systém; vegetační střecha; dřevěný vazník; podsklepený dům; fotoateliér.; Bachelor thesis; family house with an establishment; pent roof; brick system; vegetative roof; wooden trusses; basement house; photo studio.